Real-time observation of fluid flows in tissue during stress relaxation using Raman spectroscopy. (26th July 2017) - Parkes, Maria; Cann, Philippa; Jeffers, Jonathan
Abstract: This paper outlines a technique to measure fluid levels in articular cartilage tissue during an unconfined stress relaxation test. A time series of Raman spectrum were recorded during relaxation and the changes in the specific Raman spectral bands assigned to water and protein were monitored to determine the fluid content of the tissue. After 1000 s unconfined compression the fluid content of the tissue is reduced by an average of 3.9% ± 1.7%. The reduction in fluid content during compression varies between samples but does not significantly increase with increasing strain. Further development of this technique will allow mapping of fluid distribution and flows during dynamic testing making it a powerful tool to understand the role of interstitial fluid in the functional performance of cartilage.